2018
DOI: 10.1111/zph.12534
|View full text |Cite
|
Sign up to set email alerts
|

A systematic knowledge synthesis on the spatial dimensions of Q fever epidemics

Abstract: From 2007 through 2010, the Netherlands experienced the largest Q fever epidemic ever reported. This study integrates the outcomes of a multidisciplinary research programme on spatial airborne transmission of Coxiella burnetii and reflects these outcomes in relation to other scientific Q fever studies worldwide. We have identified lessons learned and remaining knowledge gaps. This synthesis was structured according to the four steps of quantitative microbial risk assessment (QMRA): (a) Rapid source identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 81 publications
(140 reference statements)
0
16
0
Order By: Relevance
“…In the case of infectious disease outbreaks, air measurements can either prospectively or retrospectively contribute to source identification and source attribution. 9…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of infectious disease outbreaks, air measurements can either prospectively or retrospectively contribute to source identification and source attribution. 9…”
Section: Discussionmentioning
confidence: 99%
“…18 Only for Q fever, the transmission of the causal bacteria via air has been firmly established; for other zoonotic diseases (campylobacteriosis, methicillin-resistant Staphylococcus aureus (MRSA) colonization), this is still to be ascertained. 1,9 Besides infectious diseases, other health outcomes like respiratory health effects and atopic sensitization were found to be associated with livestock density. 1014 The underlying causal mechanisms for these more general health outcomes are unknown; microbial air pollution is suggested to potentially play a role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent time, Q fever has received an increase in publicity on the potential source of transmission and possible preventative measures in both livestock and humans (see, for example, [11,16] and the references therein). e research by De Rooij et al [17] suggested that during any future epidemics, attention should be placed on a rapid source of identification, quantification of emission, accurate data collection, and smooth data exchange amongst relevant actors to enable effective risk assessment and risk management. Mori and Roest [18] pointed out that in achieving an effective control and management, there should be collective expertise from other scientific disciplines and stakeholder so that the expectations of farmers and the wider community can be met on the spread of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…When human Q fever incidence was combined with data about C. burnetii status of farms, spatial relationships were identified: with increasing distance from C. burnetii positive farms, decreasing human Q fever incidence was observed 8 , 9 . This relationship has been thoroughly investigated in the past, focussing on environmental conditions 10 , 11 , meteorological conditions 12 , and mapping cases in relation to C. burnetii positive farms 2 , 13 as recently reviewed by De Rooij et al 5 .…”
Section: Introductionmentioning
confidence: 99%